Impact of Combined Hormonal Contraceptive Use on Weight Loss: A Secondary Analysis of a Behavioral Weight‐Loss Trial. Issue 6 (22nd May 2020) - Caldwell, Ann E.; Zaman, Adnin; Ostendorf, Danielle M.; Pan, Zhaoxing; Swanson, Bryan B.; Phelan, Suzanne; Wyatt, Holly R.; Bessesen, Daniel H.; Melanson, Edward L.; Catenacci, Victoria A.
Abstract : Objective: This study aimed to perform a preliminary investigation of the impact of combined hormonal contraceptive (CHC) use on weight loss during an 18‐month behavioral weight‐loss trial. Methods: Adults ( n = 170; 18‐55 years; BMI 27‐42 kg/m 2 ) received a weight‐loss intervention that included a reduced‐calorie diet, a progressive exercise prescription, and group‐based behavioral support. Premenopausal women ( n = 110) were classified as CHC users (CHC, n = 17) or non‐CHC users (non‐CHC, n = 93). Changes in weight were examined within groups using a linear mixed model, adjusted for age and randomized group assignment. Results: At 6 M, weight was reduced from baseline in both CHC (mean, −6.7 kg; 95% CI: −9.8 to −3.7 kg) and non‐CHC (−9.1 kg; −9.1 to −6.4 kg). Between 6 and 18 M, CHC regained weight (4.9 kg; 0.9 to 8.9 kg), while weight remained relatively unchanged in non‐CHC (−0.1 kg; −1.8 to 1.6 kg). At 18 M, weight was relatively unchanged from baseline in CHC (−1.8 kg; −7.3 to 3.6 kg) and was reduced from baseline in non‐CHC (−7.9 kg; −10.2 to −5.5 kg). Conclusions: In this secondary data analysis, CHC use was associated with weight regain after initial weight loss. Prospective studies are needed to further understand the extent to which CHC use influences weight loss and maintenance.